CRISPR-Cas9 System In Vivo Delivery to Combat HBV - Ali, Jahanzaib; Aslam, Husnain; Yousuf , Abida (BIOEDUSCIENCE, 2023)
Background: Hepatitis B Virus (HBV) infection remains a major global health issue despite the availability of HBV vaccine. The novel CRISPR-Cas9 gene editing technology efficiently helps to cure HBV by disruption or cleavage of HBV DNA. Aims: Several in vitro and in vivo studies have demonstrated the effectiveness of HBV-specific clustered regularly interspaced short palindromic repeat (CRISPR)/associated protein 9 (CRISPR/Cas9) systems in cleaving HBV DNA. Methods: In vivo, delivery of the CRISPR/Cas9 system at target sites remains a major challenge that needs to be resolved before its clinical application in gene therapy for HBV. Results: In this review article, we comprehensively evaluate the progress, challenges, and therapeutic potential of CRISPR-Cas9 gene therapy for HBV using adeno-associated virus (AAV) vectors as delivery vehicles. Conclusion: The CRISPR-CAS9, HBV, AAV, delivery methods of CRISPR-CAS9 component in vivo, challenges, and future perspectives in harnessing this innovative technology to combat HBV infection.